Predicting and accessing metastable phases. Issue 4 (25th January 2023) - Kocevski, V.; Valdez, J. A.; Derby, B. K.; Wang, Y. Q.; Pilania, G.; Uberuaga, B. P.
Abstract : Metastable phase formation of Ln2 O3 phases was explained and successfully predicted using calculated metastable phase diagrams. Irradiation experiments of Lu2 O3 show formation of 3 phases, confirming the prediction, showing a unique behavior. Abstract : Metastable forms of matter are invaluable to our everyday lives, from advancing technology to understanding biological processes, with their unique properties often offering novel functionality. Despite their importance, synthesizing metastable phases is more art than science, often either serendipitous or trial-and-error. Insight into the amount of stored energy needed to form a metastable phase can aid in their fabrication. Here, we calculate metastable phase diagrams, from which we extract the metastability threshold – the excess energy stored in the metastable phase relative to the ground state. Using lanthanide sesquioxides (Ln2 O3 ) as a case study, we demonstrate how metastable phase diagrams provide new insight into their synthesis and irradiation behavior. We successfully predict the sequence of metastable phases induced by irradiation in Lu2 O3, forming three metastable phases with increasing irradiation fluence.